DOI: 10.31274/rtd-180813-8848
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of a direct injection diesel engine operating on methyl soyoil and methyl tallow esters

Abstract: Lubricating Oil Contamination 38 Modified Engine Configuration Fuel Storage Stability MATERIALS, EQUIPMENT AND METHODS Test Fuels Test Engine Physical and Chemical Characterization of Test fuels Viscosity 51 Surface tension Specific gravity Caloric heat value i i i page Dynamometer-Engine Instrumentation System Engine performance measurements 62 Exhaust emission data acquisition system 68 Flame ionization analyzer 70 Infrared analyzer 73 Chemiluminescent analyzer Oxygen monitor Smoke meter 77 Engine pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…2 diesel fuel. Ali [102] and Yahya [103] also found no significant difference in CO2 emissions between the biodiesel and No. 2 diesel fuel.…”
Section: Comparison Of Co2 Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 diesel fuel. Ali [102] and Yahya [103] also found no significant difference in CO2 emissions between the biodiesel and No. 2 diesel fuel.…”
Section: Comparison Of Co2 Emissionsmentioning
confidence: 99%
“…The CO emissions of the 20% blends of SME and YGME were decreased by 7.51% and 6.99%, respectively. Monyem[78], and Yahya[103] also found that biodiesel and their blends lowered CO emissions. In their study, they found 15.7% and 15.8% reductions in CO emissions compared to No.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Fuelled with non-esterified vegetable oils, they quickly experience operating problems in long-term engine used [6]. These problems among others are the formation of carbon deposits inside the engine, fuel injector fouling, sticking of piston rings, heavy gum deposits on cylinder walls, and a strong cyclic dispersion that can lead to mechanical difficulties or damages [4] [7] [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…While diesel fuel has straight or branched chain configurations, composed mostly of saturated hydrocarbons, vegetable oils are predominantly formed by (about 95%) triglycerides which are also composed of saturated or unsaturated fatty acids. The highest degree of unsaturation makes vegetable oils susceptible to oxidation leading to free radical formation and polymerization [10]. This polymerization can either be an oxidative polymerization in storage, pressures preceding combustion [10].…”
Section: Introductionmentioning
confidence: 99%